Platform Based Digital Business Model Analysis to Enhance Sustainable Organizational Competitiveness - Marviola Hardini; Suca Rusdian; Dwi Nur Ramadhan; Maulana Arif Komara; Cristiano Gatot Wagner (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2026)
The development of the digital economy encourages companies to adopt platform-based business models that connect consumers, merchants, service partners, and technology providers within an integrated ecosystem. This study aims to analyze digital platform business models in enhancing sustainable competitiveness in Indonesia. This study uses a descriptive qualitative approach through literature review, documentation analysis, and digital observation. The analytical framework includes the Business Model Canvas, SWOT Analysis, and Triple Bottom Line to examine value creation, strategic position, and sustainability contributions. Objects include GoTo, Shopee, Tokopedia, and TikTok Shop Indonesia. The findings indicate that network effects, ecosystem integration, artificial intelligence-based personalization, data analytics, and partnerships are key factors in building competitive advantage. SWOT Analysis shows that platform strengths lie in user scale and ecosystem breadth, while the challenges include profitability pressure, promotional dependence, regulation, and global competition. From a sustainability perspective, digital platforms contribute to MSME empowerment, financial inclusion, operational efficiency, green logistics, and ESG implementation. Triple Bottom Line integration relates to SDGs 8, SDGs 9, and SDGs 12. These findings emphasize the importance of balancing economic performance, social impact, and environmental responsibility in Indonesia’s digital platform strategies. Practically, the results support stronger ecosystem governance and inclusive sustainable national economic policies.